STUDI KOORDINASI KERJA RELE DIFERENSIAL DAN RELE RESTRICTED EARTH FAULT SETELAH UPRATING PADA TRANSFORMATOR II DI GI KAPAL - I Made Dwi Cahyadi Jaya; I Gede Dyana Arjana; A.A Gede Maharta Pemayun (Jurnal SPEKTRUM, 2018)
The differential relay on the power transformer II in the Kapal Substation has a sensitivity setting of 30% to the nominal current of winding. Fault current that occurs below setting is not detected because the fault current has not reached the set limit. To overcome the fault current it is equipped with REF relay that has sensitivity below 30%. The analysis was performed by calculation method according to the relay setting manual. The results of sensitivity setting of REF relay is 382.75 A or fault point at 22.09% of the transformer winding, while the differential relay is 519.6 A or fault point at 30% of the transformer winding. The calculation result shows that the first to work is the REF relay than the differential relay. So the fault on the transformer winding is overcome by the REF relay.